2021
DOI: 10.1038/s42003-021-02101-5
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved spectroscopic and electrophysiological data reveal insights in the gating mechanism of anion channelrhodopsin

Abstract: Channelrhodopsins are widely used in optogenetic applications. High photocurrents and low current inactivation levels are desirable. Two parallel photocycles evoked by different retinal conformations cause cation-conducting channelrhodopsin-2 (CrChR2) inactivation: one with efficient conductivity; one with low conductivity. Given the longer half-life of the low conducting photocycle intermediates, which accumulate under continuous illumination, resulting in a largely reduced photocurrent. Here, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…The calculated protonation pattern shows that Asp234 is deprotonated in the wild-type Gt ACR1 even using the MD-generated conformations with protonated Glu68/protonated Asp234 or deprotonated Glu68/protonated Asp234 ( Table 1 , Supplementary file 1B , Figure 2—figure supplement 1 ). These results suggest that deprotonation of Asp234, ‘the only residue directly interacting with the protonated Schiff base ( Li et al, 2019 )’, is a prerequisite to stabilize the protonated Schiff base, as suggested by Dreier et al, 2021 .…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The calculated protonation pattern shows that Asp234 is deprotonated in the wild-type Gt ACR1 even using the MD-generated conformations with protonated Glu68/protonated Asp234 or deprotonated Glu68/protonated Asp234 ( Table 1 , Supplementary file 1B , Figure 2—figure supplement 1 ). These results suggest that deprotonation of Asp234, ‘the only residue directly interacting with the protonated Schiff base ( Li et al, 2019 )’, is a prerequisite to stabilize the protonated Schiff base, as suggested by Dreier et al, 2021 .…”
Section: Resultsmentioning
confidence: 87%
“…The C=O stretching frequencies of 1740 (–)/1732 (+) cm –1 for protonated Asp234 at 77 K observed by Kim et al, 2018 were not observed at 293 K by Dreier et al, 2021 . In addition, MD simulations indicated that the H-bond network that involves Tyr72, Tyr207, and Asp234 was stable with deprotonated Asp234 but unstable with protonated Asp234 ( Dreier et al, 2021 ). Indeed, the presence of deprotonated Asp234 was already suggested based on the homology modeling of Gt ACR2 ( Kojima et al, 2018 ) before the crystal structures of Gt ACR1 were reported.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations